(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Prostate cancer is the number one cancer by incidence in males of increasing age & second by mortality throughout the world. Many known etiological factors are associated with increased risk of prostatic carcinoma including male hormone & its active metabolites, genetic predisposition (BRCA2, inherited polymorphism of some transcription factors), racial difference, environmental factors, food habits etc, Recently an association of importance has been given to molecular level changes; inflammatory cytokines, trace elements like zinc with prostate cancer. Diagnostic modalities & treatment facilities are important for better management & giving improved quality of life to the patients. The present review article highlights some of these findings on prostate cancer namely genetic factors, Highfatty diet, Hormone, medication, sexual activity, inflammatory cytokines, trace element zinc, PSA. These will lead to in hand better understanding of the pathophysiology of prostate cancer. Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 36-44